A review: underutilized plant of Sabah and its potential value - Nor Amirah Shamsudin; Poh, Lucky Wah Goh; Mohd Khalizan Sabullah; Suraya Abdul Sani; Rahmath Abdulla; Jualang Azlan Gansau (Bentham Science Publishers B.V., 2021)
Underutilized plants are referred to a plant species which their potential is not fully utilized yet and they are usually found abundantly in certain local area but globally rare. Sabah is known for a high biodiversity and contains many underutilized plants. To our knowledge, this is the first review is to provide an overview information of medicinal value and pharmacological properties of underutilized plant in Sabah. Extract and metabolites in different part of several underutilized plant contains multiple beneficial bioactive compounds and exploitation of these compounds was supported by additional data which plays various biological activities including anti-atherosclerotic, anti-cancer, anti-hypercholesterolemic and anti-ulcerogenic. A handful of pharmacological studies on the natural product these underutilized plants have conclusively outlined the mode of action in treatment of several diseases and in other health aspects. This paper limits its scope to review and highlight the potential of using underutilized plants in Sabah only which could serve as reliable resource for health product development in pharmaceutical and nutraceutical through continuous discovering of more active and sustainable resources as well as ingredients for food and medicine.